Comparative study of image quality between T2W-FRFSE and T2W-PROPELLER based on respiratory patterns at abdominal MRI - 박호성 (The Graduate School, Ajou University, 2024)
본 연구는 복부 자기공명영상 (Abdominal Magnetic Resonance Imaging: ABD MRI) 검사 시 종양과 낭종등 다양한 질환 진단에 사용되는 T2W-FRFSE와 T2W-PROPELLER 기법을 호흡의 패턴에 따라 화질을 비교하고 평가했다. 연구 대상 및 방법은 2018년 9월 1일부터 2019년 2월 27일까지 본원에서 ABD MRI 검사를 받은 총 238명 (남자 131명, 여자 107명)의 환자를 후향적으로 분석하였다. 장비는 MRI Scanner (GE™ Signa HDxt 1.5T), Coil은 12ch Body Array를 사용하였고, Axial T2W-FRFSE, Axial T2W-PROPELLER 검사 기법을 시행하였다. 검사는 Respiratory Triggering 방법을 사용하였고, 그룹은 호흡 방식에 따라 Normal Breathing (Eupnea), Rapid Breathing (Tachypnea, Hyperpnea), Slow Breathing (Bradypnea), Irregular Breathing (Biots, Cheyne Stokes)으로 나누었다. 영상의 화질 평가는 SNR, CNR, BRISQUE를 활용하여 정량 평가하였고, SNR, CNR 평가는 Image J (Ver. 1.47v, National Institutes of Health, LOCI, University of Wisconsin, USA)를 사용하였으며, BRISQUE 화질 평가는 Mathworks에서 개발한 공학용 소프트웨어 Matlab™ (Ver9.14.0.2206163, 64bit, Feb 22, 2023 Mathworks, Natick, USA)의 BRISQUE Model을 활용하였다. 정성 평가는 복부 영상의학과 판독의 2명이 리커트 5점 척도를 통해 평가하였고, 화질 평가는 네 가지 (Ghost Artifacts, Sharpness, Noise, Overall Quality)로 평가하였다. 통계학적 분석은 R Studio (Ver. 2023.06.2.+561, R Studio, Inc. Boston, USA)을 사용하여 t-test, Wilcoxon signed rank test를 이용하여 통계 분석하였다. 해당 연구는 아주대학교 의료원 기관 연구윤리심의위원회에서 승인되었다 (AJOUIRB-MDB-2019-525)._x000D_ SNR의 정량 평가 결과는 Normal Breathing, Slow Breathing 그룹의 경우에 FRFSE 기법이 PROPELLER 기법에 비하여 유의미하게 높았으나 (107.84±43.54 vs. 74.63±30.12 p=0.001, 107.38±62.49 vs. 77.69±54.95, p=0.001), Rapid Breathing, Irregular Breathing 그룹의 경우에는 유의미하게 낮았다 (91.25±77.46 vs. 122.31±103.63, p=0.001, 72.45±39.10 vs. 114.71±133.72, p=0.001). CNR의 정량 평가 결과는 Normal Breathing, Slow Breathing 그룹의 경우에 FRFSE 기법이 PROPELLER 기법에 비하여 유의미하게 높았으나 (94.64±51.64 vs. 76.39±43.72, p=0.05, 73.79±52.49 vs. 50.95±40.09, p=0.001), Rapid Breathing, Irregular Breathing 그룹의 경우에는 유의미하게 낮았다 (61.35±49.40 vs. 80.21±49.07, p=0.05, 55.19±33.13 vs. 85.23±41.38, p=0.05). BRISQUE의 정량 평가 결과는 Normal Breathing, Slow Breathing 그룹의 경우에는 FRFSE 기법이 PROPELLER 기법에 비하여 유의미하게 높았으나 (42.91±8.44 vs. 32.75±7.88, p=0.001, 44.04±10.45 vs. 32.31±6.68, p=0.001), Rapid Breathing. Irregular Breathing 그룹의 경우에는 유의미하게 낮았다 (32.18±9.26 vs. 39.75±10.07, p=0.001, 30.09±8.33 vs. 38.43±6.35, p=0.001). Ghost Artifacts의 정성 평가 결과는 Normal Breathing, Slow Breathing 그룹의 경우에 FRFSE 기법과 PROPELLER 기법이 유의미한 차이가 없었으나 (4.51±0.61 vs. 4.58±0.53, p=0.375, 4.39±0.66 vs. 4.25±0.59, p=0.404), Rapid Breathing, Irregular Breathing 그룹의 경우에는 유의미하게 낮았다 (1.97±0.79 vs. 4.56±0.57, p=0.001, 2.79±0.70 vs. 4.41±0.64, p=0.001). Sharpness of Liver의 정성 평가 결과는 Normal Breathing, Slow Breathing 그룹의 경우에 FRFSE 기법이 PROPELLER 기법에 비하여 유의미하게 높았으나 (4.38±0.56 vs. 3.91±1.04, p=0.05, 4.59±0.61 vs. 4.10±0.91, p=0.05), Rapid Breathing, Irregular Breathing 그룹의 경우에는 유의미하게 낮았다 (3.58±0.89 vs. 4.46±0.65, p=0.001, 3.27±0.93 vs. 4.40±0.66, p=0.001). Noise의 정성 평가 결과는 Normal Breathing, Slow Breathing 그룹의 경우에 FRFSE 기법이 PROPELLER 기법에 비하여 유의미하게 높았으나 (4.19±0.62 vs. 3.58±1.03, p=0.05, 4.58±0.59 vs. 3.97±0.80, p=0.001), Rapid Breathing, Irregular Breathing 그룹의 경우에는 유의미하게 낮았다 (3.48±0.71 vs. 4.55±0.50, p=0.001, 3.29±0.95 vs. 4.51±0.67, p=0.001). Overall Quality의 정성 평가 결과는 Normal Breathing, Slow Breathing그룹의 경우에 FRFSE 기법이 PROPELLER 기법에 비하여 유의미하게 높았으나 (4.09±0.69 vs. 3.53±0.82, p=0.05, 4.61±0.58 vs. 3.92±0.78, p=0.01), Rapid Breathing, Irregular Breathing 그룹의 경우에는 유의미하게 낮았다 (3.53±0.82 vs. 4.54±0.57, p=0.001, 3.03±0.96 vs. 4.40±0.66, p=0.001). _x000D_ 이상의 결과를 통해 ABD MRI 검사 시 환자의 호흡 패턴에 따라 T2W-FRFSE, T2W-PROPELLER 기법의 화질 차이가 발생함을 확인하였다. T2W-FRFSE 기법은 Normal Breathing (Eupnea), Slow Breathing (Bradypnea)의 그룹에서 화질이 우수하였고, T2W-PROPELLER 기법은 Rapid Breathing (Tachypnea, Hyperpnea), Irregular Breathing (Biots, Cheyne Stokes) 그룹에서 화질이 우수하였다. 결과적으로 ABD MRI Axial T2W FSE 검사 시 환자의 호흡 패턴은 영상의 품질에 영향을 미치기 때문에 환자의 호흡 패턴 (Respiratory Patterns)에 따라 다른 기법의 선택이 필요하다._x000D_ _x000D_ 핵심단어: ABD MRI, FRFSE, PROPELLER, Respiratory Patterns, BRISQUE_x000D_ _x000D_ 약어:　_x000D_ ·ABD MRI (Abdominal Magnetic Resonance Imaging)_x000D_ ·FRFSE (Fast Recovery Fast Spin Echo)_x000D_ ·PROPELLER (Periodically Rotated Overlapping Parallel Lines with Enhanced Reconstruction) _x000D_ ·SNR (Signal-to-Noise Ratio)_x000D_ ·CNR (Contrast-to-Noise Ratio) _x000D_ ·T2W (T2 Weighted)_x000D_ ·BRISQUE (Blind/Referenceless Image Spatial Quality Evaluator)|Purpose: To compare and evaluate the image quality of T2W-FRFSE and T2W-PROPELLER techniques used to diagnose various conditions such as tumors and cysts during abdominal magnetic resonance imaging (MRI) examinations based on respiratory patterns._x000D_ _x000D_ Subjects and Methods: This study was a retrospective analysis of a total of 238 patients (Male: 131, Female: 107) who underwent abdominal MRI examinations in our hospital from September 1, 2018, to February 27, 2019. The equipment used was GE™ Signa HDxt 1.5T, with a 12-channel Body Array coil, and Axial T2W-FRFSE and Axial T2W-PROPELLER techniques were employed. A respiratory triggering method was used, and the groups were divided into Normal Breathing (Eupnea), Rapid Breathing (Tachypnea, Hyperpnea), Slow Breathing (Bradypnea), and Irregular Breathing (Biot's, Cheyne-Stokes) according to the respiratory patterns. Image quality was evaluated quantitatively using SNR, CNR, and BRISQUE. SNR and CNR were evaluated using ImageJ (Ver. 1.47v, National Institutes of Health, LOCI, University of Wisconsin, USA), and the BRISQUE image quality assessment was performed using the BRISQUE Model in Matlab™ (Ver. 9.14.0.2206163, 64-bit, Feb 22, 2023, MathWorks, Natick, USA). The qualitative assessment was conducted by two abdominal radiologists using a 5-point Likert scale, and the image quality was evaluated based on four factors: Ghost Artifacts, Sharpness, Noise, and Overall Quality. Statistical analysis was performed using t-test and Wilcoxon signed-rank test statistical methods in R Studio (Ver. 2023.06.2+561, R Studio, Inc., Boston, USA). This study was approved by the Institutional Review Board of Ajou University Medical Center (AJOUIRB-MDB-2019-525)._x000D_ _x000D_ Results: The results of the quantitative evaluation of SNR were significantly higher in the FRFSE compared to the PROPELLER in the Normal Breathing and Slow Breathing groups (107.84±43.54 vs. 74.63±30.12, p=0.001; 107.38±62.49 vs. 77.69±54.95, p=0.001), but significantly lower in the Rapid Breathing and Irregular Breathing groups (91.25±77.46 vs. 122.31±103.63, p=0.001; 72.45±39.10 vs. 114.71±133.72, p=0.001). The results of the quantitative assessment of CNR were significantly higher in the FRFSE compared to the PROPELLER in the Normal Breathing and Slow Breathing groups (94.64±51.64 vs. 76.39±43.72, p=0.05; 73.79±52.49 vs. 50.95±40.09, p=0.001), but significantly lower in the Rapid Breathing and Irregular Breathing groups (61.35±49.40 vs. 80.21±49.07, p=0.05; 55.19±33.13 vs. 85.23±41.38, p=0.05). The quantitative evaluation of BRISQUE showed that the FRFSE was significantly higher than the PROPELLER in the Normal Breathing and Slow Breathing groups (42.91±8.44 vs. 32.75±7.88, p=0.001; 44.04±10.45 vs. 32.31±6.68, p=0.001), but not in the Rapid Breathing and Irregular Breathing groups, where it was significantly lower (32.18±9.26 vs. 39.75±10.07, p=0.001; 30.09±8.33 vs. 38.43±6.35, p=0.001). The results of the qualitative assessment of ghost artifacts were not significantly different between the FRFSE and PROPELLER for the Normal Breathing and Slow Breathing groups (4.51±0.61 vs. 4.58±0.53, p=0.375; 4.39±0.66 vs. 4.25±0.59, p=0.404), but were significantly lower in the Rapid Breathing and Irregular Breathing groups (1.97±0.79 vs. 4.56±0.57, p=0.001; 2.79±0.70 vs. 4.41±0.64, p=0.001). The results of the qualitative assessment of Sharpness of the Liver were significantly higher in the FRFSE compared to the PROPELLER in the Normal Breathing and Slow Breathing groups (4.38±0.56 vs. 3.91±1.04, p=0.05; 4.59±0.61 vs. 4.10±0.91, p=0.05), but significantly lower in the Rapid Breathing and Irregular Breathing groups (3.58±0.89 vs. 4.46±0.65, p=0.001; 3.27±0.93 vs. 4.40±0.66, p=0.001). The qualitative assessment of noise was significantly higher in the FRFSE compared to the PROPELLER for the Normal Breathing and Slow Breathing groups (4.19±0.62 vs. 3.58±1.03, p=0.05; 4.58±0.59 vs. 3.97±0.80, p=0.001), but significantly lower in the Rapid Breathing and Irregular Breathing groups (3.48±0.71 vs. 4.55±0.50, p=0.001; 3.29±0.95 vs. 4.51±0.67, p=0.001). The results of the qualitative assessment of overall quality were significantly higher in the FRFSE compared to the PROPELLER for the Normal Breathing and Slow Breathing groups (4.09±0.69 vs. 3.53±0.82, p=0.05; 4.61±0.58 vs. 3.92±0.78, p=0.01), but significantly lower in the Rapid Breathing and Irregular Breathing groups (3.53±0.82 vs. 4.54±0.57, p=0.001; 3.03±0.96 vs. 4.40±0.66, p=0.001)._x000D_ _x000D_ Conclusion: The results showed that the image quality of T2W-FRFSE and T2W-PROPELLER techniques differed depending on the patient's respiratory patterns during the abdominal MRI examination. The T2W-FRFSE technique has superior image quality in the Normal Breathing (Eupnea) and Slow Breathing (Bradypnea) groups, and the T2W-PROPELLER technique has superior image quality in the Rapid Breathing (Tachypnea, Hyperpnea) and Irregular Breathing (Biot's, Cheyne-Stokes) groups. As a result, the patient's breathing pattern during the abdominal MRI Axial T2W FSE examination affects the image quality, and different techniques should be selected according to the patient's respiratory pattern._x000D_ _x000D_ Key words: ABD MRI, FRFSE, PROPELLER, Respiratory Patterns, BRISQUE_x000D_ _x000D_ Abbreviation:　_x000D_ ·ABD MRI (Abdominal Magnetic Resonance Imaging)_x000D_ ·FRFSE (Fast Recovery Fast Spin Echo)_x000D_ ·PROPELLER (Periodically Rotated Overlapping Parallel Lines with Enhanced Reconstruction or BLADE) _x000D_ ·SNR (Signal-to-Noise Ratio)_x000D_ ·CNR (Contrast-to-Noise Ratio) _x000D_ ·T2W (T2 Weighted)_x000D_ ·BRISQUE (Blind/Referenceless Image Spatial Quality Evaluator) _x000D_
학위논문(박사)--의용공학과,2024. 8
Keywords: ABD MRI; BRISQUE; FRFSE; PROPELLER; Respiratory Trigger